Rat palatability, pharmacodynamics effect and bioavailability of mefenamic acid formulations utilizing hot-melt extrusion technology. (3rd October 2019) - Alshehri, Sultan; Shakeel, Faiyaz; Elzayat, Ehab; Almeanazel, Osaid; Altamimi, Mohammad; Shazly, Gamal; Kazi, Mohsin; Almutairy, Bjad; Alsulays, Bader; Alshetaili, Abdullah; Alalaiwe, Ahmed; Repka, Michael
Abstract: Mefenamic acid (MA) has been reported as a weakly soluble drug which presents weak in vivo absorption upon oral administration using conventional formulations. Solid dispersions (SDs) have been investigated extensively in literature for enhancing the solubility and bioavailability of weakly-soluble molecules. Hence, the aim of proposed study was to prepare MA novel formulations in the form of SDs using hot-melt extrusion technology in order to enhance its palatability, bioavailability, and pharmacodynamics effects/anti-inflammatory efficacy. Various SDs of MA were prepared using hot-melt extrusion technology, characterized physically and investigated for dissolution tests. Optimized SD formulations of MA were being subjected to palatability, pharmacodynamics, and pharmacokinetic studies in rats. Optimized SD of MA showed significant rat palatability tastes as compared with pure and marketed MA ( p  < .05). Anti-inflammatory efficacy of 20% SD and 25% SD of MA was found to be 86.44 and 89.83%, respectively, in comparison with 74.57 and 78.24% by pure MA and marketed MA, respectively. The anti-inflammatory efficacy of optimized SD was found to be significant as compared with pure and marketed MA ( p  < .05). The oral absorption of MA from optimized 20% SD was also noted as statistically significant as compared with pure MA ( p  < .05). The relative bioavailability of MA from 20 and 25% SDs was 2.97 and 2.24-folds higher than pure MA. The results of this study suggested that SDs prepared using hot-melt extrusion technology are capable to enhance palatability, anti-inflammatory efficacy, and oral bioavailability of MA in comparison with pure drug.